Analysis of Current Status in Service Level in Hotel Business in Azerbaijan - Musayeva, N.; Guliyeva, B. (Економічний вісник Донбасу, 2022)
The most important details of hotel service quality standards are the legal document approved for standardization by the state authority and the application and mandatory use of standard methods in the hotel. Standard is an example, benchmark, model, and standard-technical document reflecting the principles, requirements and rules of standard hotels. Quality in tourism is a powerful weapon for competition in international tourism market and tourists who are satisfied with the service in hotels, restaurants, service bureaus and tourist facilities of certain countries become their active promoters. The complex and complicated character of tourist service is pre-determined due to the fact that most service production is directly related to consumption, services are provided directly to tourists, tourists are offered a wide range of services and goods with different production and service technologies, service to tourists is carried out during the operation of various elements of logistics infrastructure, and servicesand goods offered to tourists are formed as a result of various types of activities. The hotel's reputation depends on the human factor and must be prepared for each hotel.
Standards for reception, accommodation and services, restaurant, bar and other departments of the hotel should be developed. The staff must have clean uniforms and neat hairdos, be professional and experienced, and demonstrate good behavior and honesty. International service standards include providing quick and flexible service to guests, accurate execution of orders, and kindness and politeness. The most important details of hotel management standards include being attentive to guests, external appearance standards, confidentiality of information, having information about the work, being patient and considerate, responsibility, and having enough staff to provide efficient and consistent service. These standards are essential for a successful hotel business, as they ensure that the quality of management is maintained in an unstable competitive environment. Найважливішими реквізитами стандартів якості готельних послуг є нормативно-правовий документ, затверджений державним органом стандартизації, а також застосування та обов'язкове використання стандартних методів у готелі. Стандарт – це зразок, еталон, модель і нормативно-технічний документ, що відображає принципи, вимоги і правила типових готелів. Якість у туризмі є потужною зброєю конкуренції на міжнародному туристичному ринку, і туристи, які задоволені обслуговуванням у готелях, ресторанах, сервісних бюро та туристичних об’єктах окремих країн, стають їх активними промоутерами. Комплексний і складний характер туристичного обслуговування зумовлений тим, що більшість послуг безпосередньо пов'язана зі споживанням, послуги надаються безпосередньо туристам, туристам пропонується широкий спектр послуг і товарів з різними технологіями виробництва і обслуговування, Обслуговування туристів здійснюється в процесі функціонування різних елементів логістичної інфраструктури, а послуги і товари, що пропонуються туристам, формуються в результаті різних видів діяльності. Репутація готелю залежить від людського фактору.
Повинні бути розроблені стандарти прийому, розміщення та обслуговування, ресторану, бару та інших підрозділів готелю. Персонал повинен мати чисту уніформу та акуратну зачіску, бути професійним і досвідченим, а також демонструвати хорошу поведінку та чесність. Міжнародні стандарти обслуговування включають швидке та гнучке обслуговування гостей, чітке виконання замовлень, доброзичливість та ввічливість. Найважливіші деталі стандартів управління готелем включають уважність до гостей, стандарти зовнішнього вигляду, конфіденційність інформації, наявність інформації про роботу, терплячість і уважність, відповідальність і наявність достатнього персоналу для ефективного та послідовного обслуговування. Ці стандарти необхідні для успішного готельного бізнесу, оскільки вони забезпечують підтримку якості менеджменту в нестабільному конкурентному середовищі.